Factors that influence the interruption of exclusive breastfeeding in nursing mothers - Daltro, Manuela Carla de Souza Lima; Vale, Uany da Cruz; Sousa, Milena Nunes Alves de; Castro, Bruna Alencar; Suárez, Larissa de Araújo Batista; Bezerra, André Luiz Dantas (Brazilian Journal of Production Engineering, 2021)
Breastfeeding is the fundamental element for children in the first months of life, in order to guarantee growth and appropriate psychological and motor development, meet the child’s nutritional needs, provide factors for the promotion and protection of maternal and child health. In addition, it will also provide the mother-child bond when the act of breastfeeding is well experienced by mothers. It was a descriptive, exploratory and quantitative field research, aiming to evaluate the factors that influence the interruption of exclusive breastfeeding in nursing mothers. The survey was performed online using a virtual questionnaire. The population was formed by all mothers of children up to 18 months of age who were participating of a group of mothers, in Patos, Paraíba. The sample consisted of the first 60 volunteers who agreed to participate, considering such sampling equivalent to 100% of the proposed total. Data collection was performed through the application of a semi-structured questionnaire containing closed questions. The sample data were analyzed, tabulated and graphed using the Statistical Package for the Social Sciences (SPSS) software. The results show that the problems that most influenced nursing women regarding the interruption of breastfeeding were nipple fissures (55%), breast engorgement (30%) and low milk production (30%). It is important to mention that a significant proportion reported pain during breastfeeding (60%) and only 17.6% reported exclusive breastfeeding only until six months. Based on this information, health professionals are expected to play a key role in helping mothers with the right orientation, making exclusive breastfeeding successful.